Antimicrobial Resistance of Enteric Salmonella in Bangui, Central African Republic - Christian Diamant Mossoro-Kpinde; Alexandre Manirakiza; Jean-Robert Mbecko; Pembé Misatou; Alain Le Faou; Thierry Frank (Journal of Tropical Medicine)
Introduction. The number of Salmonella isolated from clinical samples that are resistant to multiple antibiotics has increased worldwide. The aim of this study was to determine the prevalence of resistant Salmonella enterica isolated in Bangui. Methods. All enteric Salmonella strains isolated from patients in 2008 were identified and serotyped, and the phenotypes of resistance were determined by using the disk diffusion method. Nine resistance-associated genes, blaTEM, blaOXA, blaSHV, tetA, aadA1, catA1, dhfrA1, sul I, and sul II, were sought by genic amplification in seven S.e. Typhimurium strains. Results. The 94 strains isolated consisted of 47 S.e. Typhimurium (50%), 21 S.e. Stanleyville (22%), 18 S.e. Enteritidis (19%), 4 S.e. Dublin (4%), 4 S.e. Hadar (4%), and 1 S.e. Papuana (1%). Twenty-five (28%) were multiresistant, including 20 of the Typhimurium serovar (80%). Two main phenotypes of resistance were found: four antibiotics (56%) and to five antibiotics (40%). One S.e. Typhimurium isolate produced an extended-spectrum β-lactamase (ESBL). Only seven strains of S.e. Typhimurium could be amplified genically. Only phenotypic resistance to tetracycline and aminosides was found. Conclusion. S. Typhimurium is the predominant serovar of enteric S. enterica and is the most widely resistant. The search for resistance genes showed heterogeneity of the circulating strains.